Service life of reinforced concrete seawalls suffering from chloride attack: Theoretical modelling and analysis. (10th December 2020) - Yang, Changyi; Li, Lin; Li, Jingpei
Highlights: Theoretical method for service life prediction of RC seawall. A two-sided diffusion model is developed to for chloride penetration. Earth pressure and surface loads restrain the development of rusts and cracks. Increasing cover thickness is the most effective way to lengthen the life span. Abstract: This paper presents a theoretical model for predicting the service life of reinforced concrete (RC) seawalls under chloride attack. The developed theoretical model not only takes into account the effects of chloride-induced degradation, but also properly considers the external water and earth pressures acting on the RC seawalls. To theoretically model the service life of the RC seawall, the whole service life is divided into the initiation stage for chloride ions diffusion and the propagation stage for corrosion products development. The diffusion of chloride ions in the seawall is simulated by a two-sided chloride diffusion model on the basis of the Fick's second law, which is sufficiently validated by the corresponding ABAQUS numerical model. The propagation stage is modeled by a mechanical model that considers both the external pressures and the internal expansive pressure induced by the rust productions. Example analyses are conducted to illustrate the application of the model and investigate the effects of some key factors on the service life of RC seawall. The results show that the service life of reinforced concrete seawall increases with cover thickness, tensile strength of concrete, threshold chloride concentration, burial depth and surface load, while decreases with the increase of rebar diameter and water-cement ratio. The proposed theoretical model can serve as a theoretical base and benchmark for design and prediction of service life of coastal structures.